Modeling with AutoCAD designer - Dobek, Sandra (Irwin, 1996)
This book is intended to instruct college level students, through reference, tutorial, and exercises, on how to create solid models using AutoCAD Designer. The book begins with an overview of AutoCAD Designer and the parametric modeling process. A reference section follows, explaining the various AutoCAD Designer commands and their usage. The tutorials and chapter exercises allow the student to get hands-on experience with the various features of the program.